Seasonal Succession and Spatial Patterns of Synechococcus Microdiversity in a Salt Marsh Estuary Revealed through 16S rRNA Gene Oligotyping - Mackey, Katherine R. M.; Hunter-Cevera, Kristen; Britten, Gregory L.; Murphy, Leslie G.; Sogin, Mitchell L.; Huber, Julie A. (Frontiers in Microbiology, 2017)
Synechococcus are ubiquitous and cosmopolitan cyanobacteria that play important roles in global productivity and biogeochemical cycles. This study investigated the fine scale microdiversity, seasonal patterns, and spatial distributions of Synechococcus in estuarine waters of Little Sippewissett salt marsh (LSM) on Cape Cod, MA. The proportion of Synechococcus reads was higher in the summer than winter, and higher in coastal waters than within the estuary. Variations in the V4-V6 region of the bacterial 16S rRNA gene revealed 12 unique Synechococcus oligotypes. Two distinct communities emerged in early and late summer, each comprising a different set of statistically co-occurring Synechococcus oligotypes from different clades. The early summer community included clades I and IV, that correlated with lower temperature and higher dissolved oxygen levels. The late summer community included clades CB5, I, IV, and VI, that correlated with higher temperatures and higher salinity levels. Four rare oligotypes occurred in the late summer community and their relative abundances more strongly correlated with high salinity than did other co-occurring oligotypes. The analysis revealed that multiple, closely related oligotypes comprised certain abundant clades (e.g. clade 1 in the early summer and clade CB5 in the late summer), but the correlations between these oligotypes varied from pair to pair, suggesting they had slightly different niches despite being closely related at the clade level. Lack of tidal water exchange between sampling stations gave rise to a unique oligotype not abundant at other locations in the estuary, suggesting physical isolation plays a role in generating additional microdiversity within the community. Together, these results contribute to our understanding of the environmental and ecological factors that influence patterns of Synechococcus microbial community composition over space and time in salt marsh estuarine waters.